Pengaruh Model Pembelajaran Paired story telling Terhadap Keterampilan Menulis Karangan Narasi Pada Muatan Bahasa Indonesia Siswa Kelas V SD Negeri Kompleks IKIP I Kota Makassar - nurhaedah nurhaedah; muslimin muslimin; andini kamal (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2019)
The problem in this study was the low narrative essay writing skills of the fifth grade students of the Complex Elementary School of IKIP I Makassar City. The research objective was to find out: (1) the description of the paired story telling learning model in class V of IKIP I Elementary School, (2) description of students 'narrative essay writing skills on Indonesian language class V content of SD Negeri IKIP I Elementary School, and (3) whether the paired story telling learning model influences students' narrative essay writing skills on the fifth grade Indonesian language lesson at IKIP I Elementary School The approach taken is quantitative research type quasy experiment It is in the form of non-equivalent control group design. The independent variable in this study is the paired story telling learning model, while the dependent variable is narrative essay writing skills. The total population of 93 students namely the Va class was 46 students and the Vb class was 47 students. The research sample was 75 students conducted by drawing using the Simple Random Sampling technique with Slovin formula whose error rate was 5%. Data collection techniques using observation, tests and documentation. The data analysis technique used is descriptive analysis and inferential statistical analysis using the Statistical Package for Social Scenario (SPSS) system Version 25.0. The results of the study can be concluded that, the description of the paired story telling learning model takes place well because the percentage category for each meeting increases. So that it can be concluded that the paired story telling learning model influences the students' narrative essay writing skills in the fifth grade Indonesian language learning content at the IKIP I Makassar Complex State Elementary School.